Hysterectomy in practice: a cross-sectional insight into indications incidence and surgical approaches - Phafat, Shreya H.; Palve, Tushar T.; Thatikonda, Rajashree; Sherkhane, Vijaymala S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hysterectomy is the second most commonly performed surgical procedure among women, following cesarean section. It is indicated for a variety of benign and malignant gynecological conditions. The choice of indication, surgical route, and associated outcomes varies significantly across clinical and demographic contexts. This study aims to evaluate the clinical patterns of hysterectomy performed at a tertiary care center over six months, with a focus on patient age, common indications, surgical approach, and the requirement for blood transfusion. Methods: A retrospective, observational study was conducted in the Department of Obstetrics and Gynecology at Cama and Albless Hospital, Mumbai, in which latest fifty patients who underwent elective hysterectomy were included, based on defined inclusion and exclusion criteria. Data regarding patient demographics, indications, surgical routes, and intraoperative details were collected and analyzed using descriptive statistics. Results: Among 50 patients, the most common age group was 36-45 years (50%). Abnormal uterine bleeding was the leading indication (60%), followed by uterine fibroids (32%) and uterovaginal prolapse (14%). The abdominal route was used in 52% of cases, while 28% underwent vaginal hysterectomy and 20% underwent laparoscopic hysterectomy. Blood transfusion was required in only 12% of patients. Conclusions: Hysterectomy remains a significant gynecological intervention, most commonly indicated for abnormal uterine bleeding. It should be approached judiciously, with an emphasis on conservative and fertility-preserving alternatives where appropriate. When surgical intervention is necessary, the vaginal or minimally invasive route should be preferred whenever feasible.